Racing to retirement : understanding greyhounds' experiences of becoming pets : a dissertation presented in partial fulfilment of the requirements for the degree of Masters of Arts in Social Anthropology at Massey University, Manawatū, New Zealand - Paap, Hannah (Massey University, 2017)
This thesis is a multispecies ethnographic investigation of the transition of retired racing greyhounds to domestic pets. The key aim of this research was to understand the greyhounds’ experiences of this transition. To achieve this aim, I sought to understand the relationships that greyhounds have with both human and non-human animals over the course of their transition and how these relationships influenced the pets they became. I use the concept of rite of passage to frame greyhounds’ transition because they move from one societal role, working dogs, to another, pets, undergoing transformation in the process. My fieldwork involved a mixed methodological approach, combining participant-observation, interviews, and photography. In doing so, I gained insight into greyhounds’ own experiences of their rite of passage and not just that of the humans involved in their lives. To help me do this, I combined ethnography with ethology, the science of animal behaviour. Using ethology allowed me to learn how greyhounds used their senses to investigate and make sense of the changes in their lives, which were brought about by their transition, and how they responded to and communicated about them. I did this by interpreting their body language, body carriage, and vocalisations. Thus, greyhounds play a central role in this thesis, whilst the human is decentred. The goal of this research was to centre greyhounds, even though it is challenging to do this in text: as such this thesis is an experiment in representation. My findings suggest that greyhounds can successfully transition into pets due to breed-specific traits, such as laziness; individual dog personalities like independence; and the constructive interactions they have with both human and non-human actors. This is even though some greyhounds may find their rite of passage more difficult than others. Keywords: greyhound(s). racing dog, transition, retirement, adoption agency, (domestic) pet, multispecies ethnography, rite of passage, non-human animal, human companion, companion animal, companion species.
Keywords: Racing greyhound; Greyhounds; Psychology; Dog adoption; Research Subject Categories::VETERINARY MEDICINE::Ethology of domestic animals; Transition; Retirement; Adoption agency; (Domestic) pet; Multispecies ethnography; Rite of passage; Non-human animal; Human companion; Companion animal; Companion species